Non‐linear electrical conductivity of compositionally gradient structured zinc oxide/ethylene propylene diene monomer composites for cable accessory application - Tiandong Zhang; Huiduo Xu; Gang Liu; Chao Yin; Changhai Zhang; Yue Zhang; Yongquan Zhang; Qingguo Chi (High Voltage)
Abstract In this study, the functional gradient materials (FGMs) were the first attempt to homogenise the electric field distribution in the cable accessory, where zinc oxide particles (ZnOk) were filled into ethylene propylene diene monomer with the compositionally gradient distribution using laminating and hot‐pressing methods. The constructed FGMs with significantly improved non‐linear conductivity can avoid the electric field distortion in cable accessories. The results show that the configuration of compositionally gradient structured fillers can significantly improve the electrical conductivity of FGMs compared to the homogeneous distribution. Additionally, compositionally gradient structures of ZnOk fillers can also improve the thermal conductivity of FGM composites, which facilitates the heat dissipation of dielectric and reduces the probability of electrothermal coupling breakdown. The mechanical properties of the composites are deeply affected by the filler's content and configuration, both improved tear elongation and tensile strength can be achieved at an optimal content and gradient structure of ZnOk fillers. Finally, the simulation analysis results show that FGM composites can homogenise the electric field more efficiently in comparison with homogeneous composites. This work demonstrates that compositionally gradient structures can improve the utilisation of functional fillers and develop the FGM composites for high‐voltage direct current cable accessory applications.